Dukungan Sosial Dalam Proses Penyembuhan Orang Dengan Gangguan Jiwa di UPT Rehabilitasi Sosial Bina Laras Kediri - Maisun, Rahma Habsari; Subardhini, Meiti; Herlina, Elin (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2024)
Research on Social Support in the Healing Process for People with Mental Disorders aims to obtain an overview of emotional support, appreciation support, instrumental support, informational support and group support at the Bina Laras Kediri Social Rehabilitation UPT for People with Mental Disorders. This research uses qualitative research methods with a descriptive approach. The number of informants in this research was 5 people with the technique of determining informants using purposive sampling. The data collection techniques used were: (1) interviews; (2) observation; (3) documentation study. Checking the validity of the data is carried out through: (1) trust test; (2) transferability test; (3) dependency test; and (4) certainty test. The results of the research show that the social support provided by the Bina Laras Kediri Social Rehabilitation UPT is quite good, but there is still one aspect that needs to be improved, namely the aspect of informational support, this support is still not provided optimally and effectively by social workers. Based on these problems, the researcher proposes a program, namely Friends of Hearing through Recreation Group, with the aim of helping reduce stress, improving the client's mood, improving the client's mental well-being through positive social interactions, improving social skills, building self-confidence, and providing positive experiences in the environment. which supports. The method used is Group Work with the Recreation Group group type. Keywords: Social Support, Healing Process, People with Mental Disorders